Ownership concentration, dynamic trade off theory and debt funding of business start-up - Hedia Fourati (The Journal of Entrepreneurial Finance (JEF), 2021)
This paper examines the dynamics trade-off financial structure in presence of ownership dispersion of newly created firms. Our objective is to test empirically the relevance of trade-off theory regards the debt funding behavior of business start-up. We use a sample of 200 business start-ups and the GMM panel data estimation over the period 2006-2010.
Keywords: 650; Capital Structure; Trade-off Theory; start-up; Dynamic Structure; Costs of Adjusting; Corporate Finance; ownership concentration